2011
DOI: 10.5005/jp-journals-10013-1092
|View full text |Cite
|
Sign up to set email alerts
|

Control of Anterior Epistaxis: A Comparative Analysis of the Decongestive Effect of Xylometazoline and Adrenaline in Idiopathic Epistaxis in Emergency Settings

Abstract: Objective To compare the impact of decongestive effect of xylometazoline and adrenaline in controlling active idiopathic anterior epistaxis on adult patients prior to use silver nitrate for cauterization. Study design Prospective case study. Methods The study used a prospective review of 150 consecutive adult patients diagnosed as anterior epistaxis (from August 2010 to January 2011). The study group was analyzed in three groups based on method of intervention used for management of anterior epistaxis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…18 One study found a 75% success rate with the use of oxymetazoline (strength not specified) 4 to 6 sprays per nostril given once followed by 2 sprays every 6 hours for 1 to 3 days in patients with posterior epistaxis, 18 and another reported a 65% success rate with the use of 2 sprays per Suggested treatment approach for patients in the community setting with epistaxis nostril 3 times daily for 3 to 5 days. 19 Mattoo et al 20 saw even higher rates of epistaxis resolution: 86% and 90% with topical xylometazoline 0.5% and epinephrine 1:10,000, respectively. These products were applied by packing the affected nostril(s) for 30 minutes with cotton packs soaked in the decongestant solution and are used in combination with other strategies.…”
Section: Unmedicated and Medicated Local Moisturizersmentioning
confidence: 95%
See 4 more Smart Citations
“…18 One study found a 75% success rate with the use of oxymetazoline (strength not specified) 4 to 6 sprays per nostril given once followed by 2 sprays every 6 hours for 1 to 3 days in patients with posterior epistaxis, 18 and another reported a 65% success rate with the use of 2 sprays per Suggested treatment approach for patients in the community setting with epistaxis nostril 3 times daily for 3 to 5 days. 19 Mattoo et al 20 saw even higher rates of epistaxis resolution: 86% and 90% with topical xylometazoline 0.5% and epinephrine 1:10,000, respectively. These products were applied by packing the affected nostril(s) for 30 minutes with cotton packs soaked in the decongestant solution and are used in combination with other strategies.…”
Section: Unmedicated and Medicated Local Moisturizersmentioning
confidence: 95%
“…Products for use in the community setting Numerous products have been used to manage epistaxis (Table 2). [16][17][18][19][20][21][22][23][24][25] Their role in management is dependent upon the mechanism of action in relation to the underlying cause of epistaxis. Products containing moisturizing agents may serve to mitigate further epistaxis providing dryness is problematic, whereas products that induce a local vasoconstrictor effect or assist in clot stabilization (e.g., antifibrinolytics) offer temporary approaches to halt bleeding yet may not prevent the recurrence of epistaxis, depending on the underlying etiology and subsequent treatment of epistaxis.…”
Section: General Measuresmentioning
confidence: 99%
See 3 more Smart Citations